Usability testing a practical guide for librarians - Blakiston, Rebecca, 1983- (Practical Guides for Librarians series., 2015)
Do you want to improve the usability of your library website, but feel that it is too difficult, time-consuming, or expensive? Usability Testing: A Practical Guide for Librarians will teach you how to make the case for usability testing, define your audience and their goals, select a usability testing method appropriate for your particular context, plan for an in-house usability test, conduct an effective in-house usability test, analyze usability test results, and create and implement a plan for ongoing, systematic usability testing. Step-by-step instructions, along with a myriad of examples,